Perfectionism and emotion regulation in the study of suicidal ideation in portuguese young adults - Brás, Marta (2024)
Suicide is a serious public health problem worldwide, being the culmination of a process that normally begins with suicidal ideation. Therefore, it is important to assess suicidal ideation and know its risk factors. The association between perfectionism and suicidal ideation has been widely debated in the literature. However, knowledge about the role of emotion regulation in this relationship is scarce. The main objective of this investigation was thus to study the role of emotion regulation in the relationship between perfectionism and suicidal ideation in young adults. A sample of 224 Portuguese young adults was recruited through an online form which assessed suicidal ideation, perfectionism, and emotion regulation. The results showed a positive relationship between suicidal ideation and emotion regulation difficulties. There was also a positive association between emotion regulation difficulties and perfectionism, especially regarding the strategies and dimensions of maladaptive perfectionism. The relationship between perfectionism and suicidal ideation was fully mediated by emotion regulation difficulties. Increases in emotion regulation difficulties from increased perfectionism could contribute decisively to increasing the risk of suicidal ideation. Thus, the assessment of perfectionism and emotion regulation difficulties can promote the prevention and psychological interventions for suicidal behavior.